Enhancing Bond Strength of Silicate-Based Cements with Intracanal Medicaments: A Literature Review: Intracanal Medicaments and Silicate-based Cements Bond Strength - Soltaninejad, Fatemeh; Naseri, Mandana; Alehossein, Sara; Mozdbar, Golshan; Norouzi, Hoorisa (Journal of Dental School, 2024)
Objectives Ensuring strong adhesion of silicate-based cement to dentin during root canal therapy is crucial for achieving optimal results. This review aims to evaluate how different intracanal medicaments impact the tensile bond strength of silicate-based cement in root canal treatments. Methods A thorough electronic search was performed using the PubMed and Google Scholar databases for articles published from 2000 to 2023. Results The studies included in this review evaluated the effects of various intracanal medicaments, including calcium hydroxide, chlorhexidine, triple antibiotic paste, double antibiotic paste, simvastatin, and bioactive glass, on the bond strength of silicate-based cements like mineral trioxide aggregate (MTA), Biodentine, and calcium-enriched mixture (CEM) cement. The results demonstrated varied impacts of these medicaments; some improved bond strength, while others had minimal effect. Specifically, calcium hydroxide frequently enhanced bond strength, and some antibiotic pastes showed similar benefits. In contrast, medicaments such as phenolic preparations and formaldehyde were found to have limited efficacy and potential toxicity. Conclusion The type, concentration, and application site of intracanal medicaments significantly impact bond strength. This review highlighted the potential advantages of these medicaments, including improved root canal disinfection and enhanced push-out bond strength of commonly used dental cements. These insights can help dental professionals optimize root canal treatments and improve patient outcomes.